2017
DOI: 10.1097/md.0000000000005765
|View full text |Cite
|
Sign up to set email alerts
|

Total bilirubin level may be a biomarker of nephropathy in type 2 diabetes mellitus

Abstract: Recently, the number of the studies on the relationship between the total bilirubin level (TBL) and diabetic nephropathy (DN) is increasing, but their results were not consistent. Therefore, we performed a meta-analysis to analyze the relationship between TBL and the risk of DN.We searched 5 databases before October 31, 2016, and reviewed the reference list of relevant articles. The fixed or random-effects model was used to pool risk estimates. We conducted the dose–response meta-analysis to evaluate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This approximates the results shown by others [19], who observed that total proteins level was increased in diabetics as compared to controls, while a significant reduction of serum TB level was recorded in diabetic male and female patients with both age ranges in comparison with those in control groups. These results are in accordance with those obtained by others [20,21]. The observed increase in serum total protein in diabetic patients may be explained on the basis of the elevation of different acute phase proteins, globulins, and fibrinogen in DM, which is compounded by a decrease in the fractional synthetic rate of albumin due to insulin resistance or insulin deficiency, which contribute to the elevation in plasma proteins [11].…”
Section: Serum Levels Of Liver Function Markerssupporting
confidence: 92%
“…This approximates the results shown by others [19], who observed that total proteins level was increased in diabetics as compared to controls, while a significant reduction of serum TB level was recorded in diabetic male and female patients with both age ranges in comparison with those in control groups. These results are in accordance with those obtained by others [20,21]. The observed increase in serum total protein in diabetic patients may be explained on the basis of the elevation of different acute phase proteins, globulins, and fibrinogen in DM, which is compounded by a decrease in the fractional synthetic rate of albumin due to insulin resistance or insulin deficiency, which contribute to the elevation in plasma proteins [11].…”
Section: Serum Levels Of Liver Function Markerssupporting
confidence: 92%
“…Although KIM-1, GDF-15, and TBIL were previously reported to contribute to tubular injury ( 31 , 32 ) and predict the progression of CKD ( 4 8 ). Our data did not show the causally link of these molecules with DN.…”
Section: Discussionmentioning
confidence: 99%
“…Growth differentiation factor-15 (GDF-15) was reported to be a predictor of the rapid deterioration of renal function ( 6 , 7 ). A recent meta-analysis indicated that total bilirubin level was negatively correlated with the risk of DN ( 8 ). Another meta-analysis of 25741 T2DM patients revealed that each increase of 1mg/dl of serum uric acid could increase the risk of DN by 24% ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is a potent antioxidant as well as an anti-inflammatory factor that is capable of scavenging various reactive oxygen species and free radicals 1,2, as well as counteracting oxidative stress 3,4. Many epidemiological studies have observed an inverse relationship between bilirubin and a number of pathological abnormalities, such as cardiovascular diseases 5, metabolic syndrome 6, dyslipidemia 7, and diabetes 8,9. However, we retrieved only two previous investigations studying the association between bilirubin and white blood cell (WBC) count, and there was some discordance 10,11.…”
Section: Introductionmentioning
confidence: 99%